Analysis of the Health of the Bank Using the CAMEL Method - Vera Damayanti; Dewi Silvia (MultiTech Publisher, 2023)
Using the CAMEL approach (Capital Asset Management Evaluation and Lifecycle) to assess the company's financial performance Adequacy, Resource Quality, The board Quality, Earnings furthermore, Liquidity). The CAMEL method is used as an analytical framework that can give top to bottom insight into the health of the bank and the potential dangers that might be looked by the bank. This study used a quantitative approach by analyzing each component of CAMEL separatelythe potential dangers that might be looked by the comes from the yearly fiscal reports of Bank PT BRI Tbk. for the 2020-2022 period. The aftereffects of the examination show that Bank BRI has an adequate level of capital adequacy, showing the bank's stability and ability to deal with potential losses. The bank's asset quality is also relatively good, indicating effective credit risk management. In addition, the quality of bank management is also considered good, with effective policies and good risk management. In terms of revenue, Bank BRI has a healthy performance, showing the ability to generate profits consistently.